Silent perforation and migration of IUCD: A diagnostic challenge in patients with pain abdomen: A case report - Srirambhatla, Annapurna; Narayanam, Srinivasa; Kannepalli, Poornima Lakshmi (Indian Journal of Case Reports, 2021)
Secondary perforations of intrauterine contraceptive devices (IUCD) may be clinically silent. The patient may not report the missing threads due to a lack of acute symptoms or under the impression that the device could have been expelled. We present a case of a 42-year-old lady treated for renal cell carcinoma and presenting with recurrent right lower quadrant abdominal pain for 2 years. Ultrasound scans did not reveal any abnormality. A plain computed tomography (CT) revealed a migrated IUCD embedded in the omentum with adjacent inflammation. Although CT is not the modality of choice in the diagnosis of migrated IUCD, it proved helpful in diagnosing this case as history was not forthcoming. This case highlights the diagnostic dilemma faced in cases of silent IUCD migration presenting with pain abdomen. It is important to counsel the patient at the time of IUCD insertion for the early recognition of missing devices and prompt diagnosis of complications.